Problemy polovogo dimorfizma v sporte vysshikh dostizheniii - Shakhlina, A. G. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The system approach has been used to study medical and biological properties of the organism of sports-women, the effect exerted on the organism by the cyclic changes in the hormonal status and neurohormonal regulation of physiological systems, the function respiration system in particular, physical working capacity.